LA CONSTRUCCIÓN DEL APRENDIZAJE CULTURAL: ANÁLISIS DE LAS PERCEPCIONES DEL PROFESORADO DE INGLÉS - Méndez García, María del Carmen; Castro Prieto, Paloma; Sercu, Lies (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Today teaching and learning tend to be viewed in a constructivist and/or (social) constructivist perspective. Learning is regarded as a process of meaning construction in which the individual actively participates in interaction with the learning environment. From a constructivist perspective, culture learning is considered as an active process which allows the students the transformation of knowledge. The teacher’s role as mediator in this process requires the development of abilities to scaffold learning and guide learners towards autonomy and independent culture learning. In this paper we report a research project which investigated to what extent Spanish EFL teachers depart from their learners current level of familiarity with the target culture and to what extent teachers current approaches to the teaching of culture in secondary education can be characterised as constructivist. The results show that the foreign culture teaching approach adopted by these teachers can only in part be characterised as scaffolding the learning process towards learner autonomy.